Analisis Literasi Keuangan Dan Kontribusi Bantuan Langsung Tunai Pada Masa Pandemi Covid-19 Terhadap Ketahanan Ekonomi Keluarga Didesa Cipete Kecamatan Curug Kota Serang - Lamsah Lamsah; Muhamad Arifin (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
The purpose of this study was to analyze the effect of financial literacy and Direct Cash Assistance (BLT) during the Covid-19 Pandemic on Family Economic resilience in Cipete Village, Curug District, Serang City. The implementation of various policies was carried out by the government as an effort to reduce the transmission of Covid-19, the existence of this outbreak had a negative impact on the economy in Indonesia. especially for the poor or unable. This research is a qualitative description research and the population used in this study is the people who get Direct Cash Assistance (BLT) in Cipete Village, Curug District, Serang City. The sampling technique used was random sampling in the community who received the Direct Cash Assistance, where the minimum sample size was based on the use of the Slovin formula, namely 100 samples from the entire population. Methods of data collection using a questionnaire. The results showed that partially Financial Literacy had an effect but not significantly on family economic resilience, while partially Direct Cash Assistance had a significant effect on family economic resilience. Simultaneously Financial Literacy and Direct Cash Assistance affect family economic resilience.